Studi Penelusuran Aliran Pada Sungai Krueng Meureubo Kecamatan Meurebo Kabupaten Aceh Barat - Muhammad Ikhsan; Meidia Refiyanni; Dewita Nazimi (Universitas Teuku Umar, 2018)
Flood routing can be called a procedure for estimating / predicting the time and magnitude of the flood that will occur at a point based on known data. The purpose of this research is to know the flow of river flow in Krueng Meureubo watershed and to know characteristic of hydrograph in the upstream and downstream by using Muskingum method. The data used in this research is secondary data that is daily rainfall data and topographic map. The highest intensity of rainfall occurred in the 10th return period and the lowest occurred in the second return period. Coefficient value (k) 3400 s and value x 0.462. The results of this study indicate that the peak inflow discharge at 36,543 m3 / s, while the peak discharge outflow 35.934 m3 / s. The flow hydrograph with the Muskingum method shows that the difference in the initial value of the outflow input does not have a large effect on the resulting discharge, the resulting debit value is almost equal to the end of the hydrograph. From the results of this study is expected to be a reference for related parties to take preventive action or reduce the impact of flood disaster, and build an early warning system so that people can have a preparedness system. Keywords—Flood, Flow Routing, Krueng Meureubo River, Muskingum